Estimation of the drag coefficient of mine imitator in longitudinal air flow using numerical methods - Fedaravičius, Algimantas; Jonevičius, Vaclovas; Kilikevičius, Sigitas; Paukštaitis, Linas; Šaulys, Povilas (Transport, 2011)
One of the most important measures to reduce the cost of preparing mortar units is the use of mortar shooting trainers operating according to the ‘shell in shell’ principle that best meets the needs of military forces. When increasing the efficiency of using equipment for mortar shooting training and seeking to reduce their production costs, further research on external ballistics is strictly necessary in order to improve the structural parameters of mine imitators. With the help of finite element modelling techniques, this article investigates air flow over mortar mine imitators. In order to achieve the aim, a package of Mechanical Desktop Software was used for creating a dimensional model of mine imitator the model of which was imported into ANSYS CFX and a finite element numerical model was generated. Considering the literary sources of experimental studies, SST turbulence model generating the results closest to those of experimental research was selected. After modelling, air drag force influencing mine imitator and the drag coefficient at different air flow speed were established.First Published Online: 07 Jul 2011